Eco-friendly Assessment of Anode Hexagonal Configuration on the Migration of Metal Ions - Abbas, Israa Talib; Amal Hamza Khalil; Nisren jasim Almansori (International Journal of Computational and Experimental Science and Engineering, 2025)
The remediation process used to extract different types of contaminants from the contaminated soil by applying an electrical field is the electro-kinetic technique. Experiments were performed under unenhanced, enhanced, and acidified conditions: the enhancement condition used 1 M acetic acid in the cathode chamber as a catholyte solution with pH regulated between 3 and 4, while distilled water served as the anolyte solution. The unenhanced condition used distilled water in the cathode chamber as the catholyte solution, without pH control, and distilled water as the anolyte solution, together with acidified contaminated soil. The highest removal efficiency rate of cadmium was recorded in the acidified soil with enhanced conditions (EK-9), reaching 65.26%, compared to the experiment with acidified contaminated soil with unenhanced conditions (EK-8), which reached 59.38%. Following that the removal efficiency of the cadmium ion obtained was equal to 56.65% in the experiment when using contaminated soil without acidification with enhanced conditions (EK-6). The lowest removal efficiency rate in this study was in the case without acidification contaminated soil with unenhanced conditions (EK-3), gaining 26.03%. This work also measured the pH and showed a significant decrease in the acidified soil conditions at enhanced conditions reaching 4.2, 5.2, and 6.1 for the samples of points measured at 3.3, 6.6, and 10 cm distances from the anode electrode for EK-9, respectively. Its highest value was reached in the experiments for contaminated soil (without acidification) at operating unenhanced conditions (EK-3), reaching 8.7, 10, and 10.7 for samples of points A1, A2, and A3, respectively.